Analisis Gaya Bahasa Pemberitaan FIFA World Cup Qatar 2022 Periode Desember di Mediaindonesia.Com dan Pemanfaatannya Sebagai Handout Kelas VII SMP - Hermawan, Dimas Putra; Huri, Daman; Sutri, Sutri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Stylistics are beautiful language used to increase the meaning effect of words that introduce and compare a particular object or thing with another more general object or thing. Language style is a word used in stories, news, magazines to add attention to a sentence so that it looks more interesting. The background of this research itself is the controversy and issues that occurred at the 2022 FIFA World Cup Qatar. The implications of language style in this research intend to find out the language style used by mediaindonesia.com as reported by mediaindonesia.com in 2020. The type of research is qualitative research, the method used in this research is the descriptive method. The data source is news on mediaindonesia.com December 2022 edition of the FIFA World Cup Qatar. The data collected is in the form of words or quotes. The data collection technique is in the form of observation techniques. The analytical technique used to analyze the data is the presentation and classification analysis model. The results of the research concluded that from the data found various types of language styles were used in writing news on mediaindonesia.com in the December 2022 FIFA World Cup Qatar December 2022 edition. There were forms of language styles that were seen to be the most dominant, such as: (1) Conflict with 45 data, (2) Comparison of 44 data, (3) Linkage of 39 data, (4) Repetition of 28 data. There is also a data classification for each of the most/dominant language styles, namely (1) Conflict with Hyperbole 9 data, (2) Comparison with Metaphor 14 data, (3) Linkage with Synecdoche 9 data, (4) Repetition with Alliteration 8 data. The results of using teaching materials are in the form of printed handouts, for class VII middle school level.